Epithelial Bone Morphogenic Protein 2 and 4 Are Indispensable for Tooth Development - Mu, Haibin; Liu, Xin; Geng, Shuoshuo; Su, Dian; Chang, Heran; Li, Lili; Jin, Han; Wang, Xiumei; Li, Ying; Zhang, Bin; Xie, Xiaohua (Frontiers in Physiology, 2021)
The Bmp2 and Bmp4 expressed in root mesenchyme were essential for the patterning and cellular differentiation of tooth root. While the role of the epithelium-derived Bmps in tooth root development had not been reported. In this study, we found that the double abrogation of Bmp2 and Bmp4 from mouse epithelium caused short root anomaly (SRA). The K14-cre;Bmp2f/f;Bmp4f/f mice exhibited a persistent Hertwig's Epithelial Root Sheath (HERS) with the reduced cell death, and the down-regulated BMP-Smad4 and Erk signaling pathways. Moreover, the Shh expression in the HERS, the Shh-Gli1 signaling and Nfic expression in the root mesenchyme of the K14-cre;Bmp2f/f;Bmp4f/f mice were also decreased, indicating a disrupted epithelium- mesenchyme interaction between HERS and root mesenchyme. Such disruption suppressed the Osx and Dspp expression in the root mesenchyme, indicating an impairment on the differentiation and maturation of root odontoblasts. The impaired differentiation and maturation of root odontoblasts could be rescued partially by transgenic Dspp. Therefore, although required in a low dosage and had a functional redundancy, the epithelial Bmp2 and Bmp4 were indispensable for the HERS degeneration, as well as the differentiation and maturation of root mesenchyme.